Anthony Norris Groves saint and pioneer : a combined study of a man of God and of the original principles and practices of the Brethren with applications to present conditions - Lang, George Henry, 1874-1958 (London, UK Thynne and co, 1939)
Includes index.
Keywords: Groves, Anthony Norris, -- 1795-1853; Brethren movement -- missions -- biography